The Effect of The Application of Good Corporate Governance (GCG) Principles on Job Satisfaction and Employee Performance - Rio Mubaraq Nazam; Rojuaniah Rojuaniah (Jurnal Indonesia Sosial Sains, 2024)
The application of good corporate governance principles is vital in all companies, particularly in the banking sector. This study examines the impact of good corporate governance on job satisfaction and employee performance, as well as the relationship between job satisfaction and employee performance. Public trust in state-owned banks is higher than that of private banks, making BNI an interesting case study. BNI, as the only state-owned bank operating globally, is known for its good corporate governance practices, as evidenced by its high CGPI score. This study focuses on permanent employees of BNI's Regional Office 15 in East Jatinegara, Jakarta. A survey was conducted among 125 respondents using SEM PLS. The results show that good corporate governance principles positively affect job satisfaction and employee performance, but job satisfaction does not directly impact employee performance. This research contributes to managerial implications, suggesting that companies can redesign positions, promotions, salaries, or rewards to enhance job satisfaction among employees. The findings of this study are expected to provide insights for managers to improve employee satisfaction and performance by implementing good corporate governance practices.